Penerapan Pendekatan Restorative Justice dalam Penyelesaian Perkara Pidana pada Tingkat Penyidikan - Jefry Rinaldi Sitanggang; Artukian Laila (INDO PUBLISHING, 2026)
This study aims to analyze the application of the restorative justice approach in resolving criminal cases at the police investigation stage, as well as the obstacles encountered during its implementation. The research employs a normative legal research method utilizing both the statute approach and the conceptual approach. The findings indicate that the application of restorative justice at the investigation stage is regulated by Indonesian National Police Regulation (Perpol) Number 8 of 2021. This approach shifts the resolution of criminal cases away from formal judicial proceedings toward deliberation among the perpetrator, the victim, and their families to reach a peace agreement focused on restoring the victim's rights. However, implementation faces challenges such as limited public understanding, the potential for abuse by unscrupulous individuals, and restrictions regarding the types of criminal offenses eligible for resolution through this mechanism.